Antibacterial activity of the seeds of Combretum quadrangulare Kurz (Combretaceae) - Natachit K. (2017)
Chemicals from seeds of Combretum quadrangulare Kurz (Combretaceae) were extracted with methanol. Purified crude methanolic extracts were done by microcrystalline cellulose column chromatography and microcrystalline cellulose preparative layers 2 times by using MeOH-H 2 O (1:1) as the developing solvent. It was found that crude methanolic extracts of 2 samples (one collected in 1997, the other in 2001), by purified column chromatographic extraction and preparative layer chromatographic residue showed antibacterial activity against gram-positive cocci and non-fermentative gram-negative bacilli better than fermentative gram-negative bacilli. From spectroscopic data and chemical tests, it was found that the isolated residues from preparative layer chromatography were steroids and flavonoid glycosides. MIC (mininum inhibitory concentration) of four sample groups for sensitive bacteria were nearly of the same level so we can use the seeds of Combretum quadrangulare Kurz directly without purification. The seeds can be used for several years if they are kept in an air-tight and dry condition.